2022
DOI: 10.3389/fimmu.2022.838530
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic, Proteomic, and Functional Assays Underline the Dual Role of Extrapallial Hemocytes in Immunity and Biomineralization in the Hard Clam Mercenaria mercenaria

Abstract: Circulating hemocytes in the hemolymph represent the backbone of innate immunity in bivalves. Hemocytes are also found in the extrapallial fluid (EPF), the space delimited between the shell and the mantle, which is the site of shell biomineralization. This study investigated the transcriptome, proteome, and function of EPF and hemolymph in the hard clam Mercenaria mercenaria. Total and differential hemocyte counts were similar between EPF and hemolymph. Overexpressed genes in the EPF were found to have domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 74 publications
(117 reference statements)
0
10
0
Order By: Relevance
“…Further, it is known that a large fraction of functional proteins present in plasma are secreted by hemocytes [50]. In fact, previous work on bivalves has shown that the plasma proteome reflects some of the proteomic make-up of circulatory hemocytes [23,71]. We had hypothesized that there would be a correlation between the two; however, this was not true for EPF and only a slightly significant correlation was found for hemolymph.…”
Section: Protein Expression Revealed Upregulated and Downregulated Pa...mentioning
confidence: 92%
See 4 more Smart Citations
“…Further, it is known that a large fraction of functional proteins present in plasma are secreted by hemocytes [50]. In fact, previous work on bivalves has shown that the plasma proteome reflects some of the proteomic make-up of circulatory hemocytes [23,71]. We had hypothesized that there would be a correlation between the two; however, this was not true for EPF and only a slightly significant correlation was found for hemolymph.…”
Section: Protein Expression Revealed Upregulated and Downregulated Pa...mentioning
confidence: 92%
“…In our study, there was a significant reduction in the phagocytic activity of agranulocytes in EPF and a reduction in cell viability for agranulocytes in both EPF and hemolymph, suggesting that there were immune costs to clam maintenance under OA. As hemocytes play dual roles in biomineralization and immunity [22,23], maintaining mineralization might come at a cost to immune function. While EPF is mostly associated with biomineralization, hemocytes in EPF are important components of the immune response [23,49,50].…”
Section: Effect Of Oa On Cellular Immune Functionsmentioning
confidence: 99%
See 3 more Smart Citations